Study Some Parameters of HCV Isolated From Sample of Hemophilic Patients in Children Welfare Teaching Hospitalin Medical City/Baghdad - alsabaq, yusra; alsaade, rayat; mohammed, eman (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s) : This study aimed at evaluating the seroprevalence of anti -HCV and studying the correlation between hemophilia and risk factors for acquiring HCV such as age , marital status & occupation among hemophilic patients . Methodology : 210 hemophilic patients in children welfare teaching hospital/medical city/Baghdad–Iraq (hemophilia center) were investigated using prepared questionnaire and tested for HCV infection, those were measuring patient’s age, hemophilia types and severity, marital status, residency and history of previous HCV infection . Results : Most hemophilic patients were hemophilia A at severe , hemophilia was at age group 20 – 29 years , the majority of patients were unmarried and from urban areas , some of them had HCV infection which was more among those had previous HCV infection . Recommendations : Health education level be increased among general population , all hemophilic patients be commitment periodic HCV infection screening also blood and its products be strictly screened .